In Search of Standard Reference Materials for ASTM E05 Fire Standards - Alvares, Norman J.; Hasegawa, Harry K. (Uncertainty in Fire Standards and What to Do About It, 2012)
The first paragraph of E-691, Standard Practice for Conducting an Inter-laboratory Study to Determine the Precision of a Test Method [ASTM E691-05, 2005, “Standard Practice for Conducting an Inter-laboratory Study to Determine the Precision of a Test Method,” ASTM Book of Standards, ASTM International, West Conshohocken, PA.] states: “Tests performed on presumably identical materials in presumably identical circumstances do not, in general, yield identical results. This is attributed to unavoidable random errors inherent in every test procedure; the factors that may influence the outcome of a test cannot all be completely controlled.” Further in the same paragraph the factors are identified: “Many different factors (apart from random variations between supposedly identical specimens) may contribute to the variability in application of a test method, including: a. the operator, b. equipment used, c. calibration of equipment, and d. environment.” The primary subjects of both the first and second paragraphs are: “presumably (supposedly) identical materials”. If, in fact, “identical materials” were available, one of the variables of testing would be eliminated because the performance of the material would be a known, which could be used for calibration procedures. Thus, any variations in the test results would be caused by a, b, or d. The Holy Grail of ASTM fire standards is the precision and bias section. ASTM regulations require precision statements in all test methods in terms of repeatability and reproducibility. However, most E05 standards do not provide precision and bias data. In fact, only 33% of E05 standards have conducted an inter-laboratory study or round robin at some time. A path forward to promote more systematic calibration procedures for E05 fire test methods and to facilitate more frequent round robin studies, is to explore the identification or development of Standard Reference Materials (SRM's) with defined properties for calibration of ASTM E05 fire tests and to validate operational performance for the same test method conducted at different facilities. Surveys of a wide range of ASTM test standards show that some of them use well-characterized materials to provide specific output data as part of their calibration procedures. In fact, SRM's have been developed for test standards; E162, E648 and E662. This paper summarizes the properties of the materials used for test calibration and their potential use as reference standards or for identifying properties important to formulating a standard material(s) for ASTM E05 fire test methods.